2014
DOI: 10.1016/j.annemergmed.2014.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Self-Interviews Improve Chlamydia and Gonorrhea Testing Among Youth in the Emergency Department

Abstract: Study Objective National guidelines recommend annual Chlamydia trachomatis and Neisseria gonorrhea screening for sexually active youth at-risk for infection. These infections have serious sequelae in women if untreated, and methods to improve testing are needed. We hypothesized that an electronic method of identifying at-risk youth would significantly increase testing for these sexually transmitted infections during emergency department (ED) visits. Methods We developed an audio-enhanced computer-assisted se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 29 publications
(24 reference statements)
0
55
0
Order By: Relevance
“…We previously reported that the ACASI identified >50% of participants as needing STI testing, and this resulted in an increase in STI testing among adolescents in our ED 19. To our knowledge, the current study is the first to both capture a sexual history via an ACASI and determine patients’ willingness to receive STI testing in the ED regardless of ED chief complaint.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…We previously reported that the ACASI identified >50% of participants as needing STI testing, and this resulted in an increase in STI testing among adolescents in our ED 19. To our knowledge, the current study is the first to both capture a sexual history via an ACASI and determine patients’ willingness to receive STI testing in the ED regardless of ED chief complaint.…”
Section: Discussionmentioning
confidence: 86%
“…Our participants reported they preferred this mode of disclosure to face-to-face interviews,19 offering options for its application even in patients whose complaints do not relate to STIs 15–18 23 24. Potential barriers to gathering sexual history information in the ED might include lack of time or the limited privacy in the ED environment.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations